2016
DOI: 10.1128/jcm.03104-15
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of a Highly Accurate Quantitative Real-Time PCR Assay for Diagnosis of Bacterial Vaginosis

Abstract: c Bacterial vaginosis (BV) is the most common gynecological infection in the United States. Diagnosis based on Amsel's criteria can be challenging and can be aided by laboratory-based testing. A standard method for diagnosis in research studies is enumeration of bacterial morphotypes of a Gram-stained vaginal smear (i.e., Nugent scoring). However, this technique is subjective, requires specialized training, and is not widely available. Therefore, a highly accurate molecular assay for the diagnosis of BV would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 36 publications
5
63
0
1
Order By: Relevance
“…A recent study has investigated the community structure of healthy and BV vaginal microbial ecosystems and detected A. vaginae only in BV group [25]. However, other studies that also investigated microbial communities associated with BV showed results that corroborate our findings [23,24].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…A recent study has investigated the community structure of healthy and BV vaginal microbial ecosystems and detected A. vaginae only in BV group [25]. However, other studies that also investigated microbial communities associated with BV showed results that corroborate our findings [23,24].…”
Section: Discussionsupporting
confidence: 82%
“…According to the literature, discrimination of Lactobacillus species by qPCR may inform about a shift on the vaginal population of this genus. Lactobacillus iners is a species associated with both healthy and abnormal vaginal microbiota [17,23,33]. Unlike Lactobacillus crispatus L. gasseri and L. jensenii, L. iners may be common and abundant in abnormal microbiota, sharing space with BV-marker organisms [3,24,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations